2011
DOI: 10.1002/pmic.201000401
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics in pancreatic cancer research

Abstract: In this review, we give an overview of the actual role of proteomic technologies in the study of pancreatic cancers (PCs). We describe PC proteomics on the basis of sample origins, i.e. tissues, body fluids, and PC cell lines. As regards PC tissues, we report the identification of a number of candidate biomarkers of precursor lesions that may allow early diagnosis of this neoplasia. Moreover, we describe cytoskeletal and hypoxia-regulated proteins that confirm the involvement of cytoskeleton modifications and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 87 publications
0
31
0
Order By: Relevance
“…The spectrum of proteins that the pancreas produces after resection of a malignant tumor may be important because, potentially, it has implications in the postoperative delivery of targeted chemotherapy and radiotherapy. 1 On the other hand, neoadjuvant treatment induces an alteration of the pancreatic proteome. Not surprisingly, nontreated organs seem to have a more thriving production of enzymes implicated in their physiologic function, such as lipase and elastase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum of proteins that the pancreas produces after resection of a malignant tumor may be important because, potentially, it has implications in the postoperative delivery of targeted chemotherapy and radiotherapy. 1 On the other hand, neoadjuvant treatment induces an alteration of the pancreatic proteome. Not surprisingly, nontreated organs seem to have a more thriving production of enzymes implicated in their physiologic function, such as lipase and elastase.…”
Section: Discussionmentioning
confidence: 99%
“…1 Proteomics can provide key information in the analysis of neoplasm onset, tumor biomarkers, and even chemotherapy effect. 2 The proteome of the normal human pancreatic juice (PJ) has been recently assessed, revealing the presence of multiple proteins related to a diversity of biological processes.…”
mentioning
confidence: 99%
“…A number of proteomics studies in pancreatic cancer have been reported[32-39]. As a subfield of proteomics, glycoproteomics uniquely focuses on analyzing glycosylated proteins to reveal glycoproteome alterations associated with pancreatic cancer.…”
Section: Glycoproteomics Methodsmentioning
confidence: 99%
“…Since the importance of the cytotoxic potential of some RNases belonging to the secretory pancreatic-type RNase super-family definitely increased in the last two decades, we investigated the effects of ONC on cells of human pancreatic adenocarcinoma, which is a particularly aggressive and devastating cancer type [21] characterized by chemoresistance to traditional therapeutic drugs including treatment with the gold standard nucleotide analogue gemcitabine (GEM; 2â€Č,2â€Č-difluoro-2â€Č-deoxycytidine) [22,23]. In particular, we aimed to explore the link between autophagy, ROS, and the antitumor activity of ONC by investigating whether this cytotoxic enzyme may trigger chemosensitivity of pancreatic adenocarcinoma cells to GEM.…”
Section: Introductionmentioning
confidence: 99%